If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying g + -1 = 5 + -1 + -9 Reorder the terms: -1 + g = 5 + -1 + -9 Combine like terms: 5 + -1 = 4 -1 + g = 4 + -9 Combine like terms: 4 + -9 = -5 -1 + g = -5 Solving -1 + g = -5 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + g = -5 + 1 Combine like terms: -1 + 1 = 0 0 + g = -5 + 1 g = -5 + 1 Combine like terms: -5 + 1 = -4 g = -4 Simplifying g = -4
| -1(p+6)= | | 36y^2-1=15 | | 3.7q-1.9-3.4q=-0.7q-1.9 | | (1-11j)4= | | 3.7q-1.9q-3.4q=-0.7q-1.9 | | 7(11-n)= | | 0.3q-1.9=-0.7q-1.9 | | 12(4-8p)= | | 7+2(a-3)= -9 | | 17(2b+3)= | | 5m+5=7m-7 | | (6y-3)5= | | 3x^3-13x^2+16=0 | | (2h-4)11= | | 3t^2+4t+1=0 | | 3(2+w)= | | g(-1)=5(-1)-9 | | 4x-6x-4=0 | | 4x(x+2)-x(3+4)=2x+18 | | 7(z-4)= | | 4x^2+21x+22=-4x+4 | | 5(x-2)=8#-3 | | 12x-41+5x+5y= | | Y=Ax-Fx-C | | z^6-z^3-2=0 | | (12x-8)+3(2x-4)= | | 10x+3=3(2x+1)-x+8 | | -x+3+9x=-2+3x+10 | | -11c=89 | | 5=-3(x+2)-4 | | 6x+3+x=2+2x+21 | | 7x(4+4x)= |